2019
DOI: 10.1002/mrd.23285
|View full text |Cite
|
Sign up to set email alerts
|

CREB activity is required for epidermal growth factor‐induced mouse cumulus expansion

Abstract: The release of a fertilizable oocyte from the ovary is dependent upon the expansion of the cumulus cells. The expansion requires cooperation between epidermal growth factor (EGF) family peptide‐activated mitogen‐activated protein kinase (MAPK)3/1 and oocyte paracrine factor‐activated‐Sma‐ and Mad‐related protein (SMAD)2/3 signaling in cumulus cells. However, the mechanism underlying (MAPK)3/1 signaling is unclear. In the present study, the EGF‐activation of EGF receptor (EGFR) induced cyclic adenosine 3′,5′‐mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 75 publications
(161 reference statements)
1
7
0
Order By: Relevance
“…EGF, cooperation with oocyte paracrine factors, promoted TGFB1 expression in cumulus cells of COCs, consistent with our recent report in mouse [ 33 ]. EGFR signaling-activated cyclic adenosine 3′,5′-monophosphate (cAMP) response element-binding protein (CREB) in mouse cumulus cells, together with oocyte paracrine factor-activated SMAD2/3, induce expansion-related gene expression and consequent cumulus expansion [ 38 ]. In the present study in pig, EGFR signaling may activate CREB, and then cooperate with oocyte paracrine factor-activated SMAD2/3 to promote TGFB1 expression in cumulus cells.…”
Section: Discussionmentioning
confidence: 99%
“…EGF, cooperation with oocyte paracrine factors, promoted TGFB1 expression in cumulus cells of COCs, consistent with our recent report in mouse [ 33 ]. EGFR signaling-activated cyclic adenosine 3′,5′-monophosphate (cAMP) response element-binding protein (CREB) in mouse cumulus cells, together with oocyte paracrine factor-activated SMAD2/3, induce expansion-related gene expression and consequent cumulus expansion [ 38 ]. In the present study in pig, EGFR signaling may activate CREB, and then cooperate with oocyte paracrine factor-activated SMAD2/3 to promote TGFB1 expression in cumulus cells.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies reported that murine embryonic fibroblasts proliferated in response to EGF only when these cells expressed PLAUR (Jo et al 2007), and EGF mitogenic activity could be blocked by PLAU gene silencing or with antibodies that block PLAU binding to PLAUR (Zhou et al 2018), suggesting a potential role of EGF/ EGFR signaling in PLAU-induced cell proliferation. Meanwhile, it has been reported that EGF increased cAMP production and amylase release in pancreatic acini (Stryjek-Kaminska et al 1995) and the EGF-activation of EGFR induced cAMP response element-binding protein (CREB) phosphorylation in cumulus cells (Zhang et al 2019), indicating a special mechanism of EGF/EGFRdependent cAMP production. Based on the above, we speculate that EGF-EGFR signaling may be the potential pathway involved in PLAU-induced intracellular cAMP production and GC proliferation.…”
Section: Discussionmentioning
confidence: 99%
“…The process of primordial follicle activation is complex and regulated by a series of signaling events. Since previously Zhang and colleagues had discovered a role for the cyclic AMP response element-binding protein (CREB) in mouse oocyte maturation and cumulus expansion (Wang et al 2016;Zhang et al 2019), they have now expanded these studies to seek a possible role for CREB activity in primordial follicle activation (Li et al 2020). In their detailed experiments, they employed multiple techniques, assays, and controls, including cultured ovaries, RNA interference, immunofluorescence and histological imaging and analysis, qRT-PCR, Western blotting, TUNEL assay for apoptosis, and chromatin immunoprecipitation.…”
Section: A Primer On Primordial Follicle Activationmentioning
confidence: 99%